From hope to horror : diplomacy and the making of the Rwanda genocide - Leader, Joyce E. (ADST-DACOR diplomats and diplomacy series., 2020)
As deputy to the U.S. ambassador in Rwanda, Joyce E. Leader witnessed the tumultuous prelude to genocide - a period of political wrangling, human rights abuses, and many levels of ominous, ever-escalating violence. This book offers her insider’s account of the nation’s efforts to move toward democracy and peace and analyzes the challenges of conducting diplomacy in settings prone to - or engaged in - armed conflict. This book traces the three-way struggle for control among Rwanda’s ethnic and regional factions. Each sought to shape democratization and peacemaking to its own advantage. The United States, hoping to encourage a peaceful transition, midwifed negotiations toward an accord. The result: a revolutionary blueprint for political and military power-sharing among Rwanda’s competing factions that met categorical rejection by the “losers” and a downward spiral into mass atrocities. Drawing on the Rwandan experience, the author proposes ways diplomacy can more effectively avert the escalation of violence by identifying the unintended consequences of policies and emphasizing conflict prevention over crisis response.